Dynamics of the Meeting Between Customary Law and Modern Law in Resolving Land Disputes in Rural Communities - Polontoh, Herry; Katjong, Kadir (PT. Hafasy Dwi Nawasena, 2024)
Land for rural communities, the majority of whom are indigenous, is a source of livelihood. Unfortunately, indigenous people often do not have official documents on land ownership, which creates legal uncertainty. This is utilized by some individuals to claim land illegally, leading to disputes. This research wants to know how the dynamics between customary law and state law in resolving land disputes, The results of data analysis show that synergy between customary law and modern law is needed to realize justice for the community. This can be done through mediation through customary justice institutions or local wisdom-based dispute resolution.